2011
DOI: 10.1103/physreve.84.011140
|View full text |Cite
|
Sign up to set email alerts
|

Hard rigid rods on a Bethe-like lattice

Abstract: We study a system of long rigid rods of fixed length k with only excluded volume interaction. We show that, contrary to the general expectation, the self-consistent field equations of the Bethe approximation do not give the exact solution of the problem on the Bethe lattice in this case. We construct a new lattice, called the random locally treelike layered lattice, which allows a dense packing of rods, and we show that the Bethe self-consistent equations are exact for this lattice. For a four-coordinated latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 42 publications
4
55
0
Order By: Relevance
“…For large enough k, the existence of the nematic phase may be rigorously proved [26]. The model may also be solved exactly on a tree-like lattice, corresponding to a Bethe approxima-tion, and shows a nematic phase for k ≥ 4, but does not exhibit a second transition [27]. Density functional theory for rods give a similar result [28].…”
Section: Introductionmentioning
confidence: 99%
“…For large enough k, the existence of the nematic phase may be rigorously proved [26]. The model may also be solved exactly on a tree-like lattice, corresponding to a Bethe approxima-tion, and shows a nematic phase for k ≥ 4, but does not exhibit a second transition [27]. Density functional theory for rods give a similar result [28].…”
Section: Introductionmentioning
confidence: 99%
“…For oriented lines in the continuum (k → ∞), a nematic phase exists at high density [22]. The only theoretical results that exist are when m = 1 and k = 2 (dimers), for which no nematic phase exists [30][31][32][33], k ≫ 1, when the existence of the nematic phase may be proved rigorously [19], and an exact solution for arbitrary k on a tree like lattice [5,23]. Less is known for other values of m and k. Simulations of rectangles of size 2 × 5 did not detect any phase transition with increasing density [34], while those of parallelepipeds on cubic lattice show layered and columnar phases, but no nematic phase [35].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we showed that a Bethe-like approximation becomes exact on a random locally tree like layered lattice, and for the 4-coordinated lattice, k min = 4. But on this lattice, the second transition is absent [20].…”
Section: Introductionmentioning
confidence: 99%